Nadi Bachao Samriddhi Lao – A forest landscape restoration initiative in Harda district, Madhya Pradesh, India. (December 2016) - Saigal, S.; Kumar, C.; Chaturvedi, R.
Abstract: One of the key challenges in forest landscape restoration (FLR) is achieving synergistic collaboration among major stakeholders. This paper analyses an innovative governance structure that brought together farmers, government agencies, civil society groups, and the private sector to plant over 2.4 million trees to stabilise riverbanks in the Harda district of Madhya Pradesh, India. The governance structure facilitated the convergence of interests of different stakeholders, thereby ensuring adequate physical, financial, and human resources for FLR. This paper reiterates the role of responsive institutional and governance structures necessary for successful FLR interventions and identifies important lessons for achieving scale.